Impatiens matthewiana, a new scapigerous balsam from Western Ghats, India - Raju, Dr Ramasubbu; Dhanraj, Felix Irudhyaraj; Arumugam, Mohanraj; Ag, Pandurangan (Phytotaxa, 2015)
Impatiens matthewiana, a new species of scapigerous balsam collected from Kerala, India is described and illustrated. This species is closely allied to I. scapiflora and I. pseudo-acualis, but differs from these two species by having moniliform tubers, rounded leaves, prominently tri-nerved lateral sepals, right basal lobe overlapping or clasping on left one, prominently two-spurred lower sepal and 4-aperturate with radial pollen. This combination of characters makes determining the relationships of I. matthewiana difficult.